1997
DOI: 10.1002/macp.1997.021980207
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and release behavior of hydrolyzable poly(etherurethane) gels derived from saccharide‐, L‐lysine‐derivatives, and poly(propylene glycol)

Abstract: Four different poly(ether urethane) gels were prepared by polyaddition of saccharide derivatives (1, 2, 3a, or 38) and poly(propy1ene glycol) with an L-lysine-derived diisocyanate, methyl (S)-2,6-diisocyanatohexanoate (4). Dibutyltin dilaurate and triisocyanate 5, that was also derived from L-lysine, were used as a catalyst and a crosslinking agent, respectively. Hydrogels containing 1, 2 or 3a were hydrolyzed in phosphate buffers (pH 5.5, 7.0, 8.0) at 27 "C, while the hydrolysis of the gel bearing 38 did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The polyurethanes obtained in this study had the projected chemical compositions (the ratio of hydrophilic segments to hydrophobic segments) and molecular weights comparable to those of experimental and commercial materials. [1][2][3][20][21][22][23][28][29][30][31][34][35][36] Their molecular weights were independent of the catalyst used. The changes in the IR spectra suggest that a higher concentration of hydrogen bonding developed in the polymers with a higher concentration of the hydrophilic component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyurethanes obtained in this study had the projected chemical compositions (the ratio of hydrophilic segments to hydrophobic segments) and molecular weights comparable to those of experimental and commercial materials. [1][2][3][20][21][22][23][28][29][30][31][34][35][36] Their molecular weights were independent of the catalyst used. The changes in the IR spectra suggest that a higher concentration of hydrogen bonding developed in the polymers with a higher concentration of the hydrophilic component.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Such moieties can be based on diols of lactic acid with ethylene diol or diethylene diol, 20 lactic acid and 1,4-butanediol, 32 or butyric acid and ethylene diol. 33 Degradable polyurethanes can also be obtained from monomers containing peptide links; 21,23,24 sugar derivatives; 22,28,30,31 the hydroxy-terminated copolymers L-lactide--caprolactone, glycolide--caprolactone, 25 -caprolactone-co-␦-valerolactone, 26,36 lysine diisocyanate, 25,27,29 poly(ethylene oxide) (PEO), and poly(-caprolactone) (PCL); and amino acid-based chain extenders. 34 This work investigates the degradation and calcification in vitro of experimental linear and biodegradable poly(ester urethane)s and poly(ester ether urethane)s with various hydrophilic-to-hydrophobic ratios for potential applications as tissue adhesion barriers, scaffolds for tissue engineering, and substitutes for cancellous bone grafts.…”
Section: Introductionmentioning
confidence: 99%
“…During our investigation of macromolecular syntheses from aldose derivatives such as saccharic and uronic acids,24–31 we found that the novel polyurethanes 12 , 13 , and 14α , prepared from D ‐glucaro‐1,4:6,3‐dilactone ( 8 ), D ‐mannaro‐1,4:6,3‐dilactone ( 9 ), and methyl α‐ D ‐glucofuranosidurono‐6,3‐lactone ( 10α ), respectively, and from hexamethylene diisocyanate ( 3a ) and methyl ( S )‐2,6‐diisocyanatohexanoate ( 3b ) could be hydrolyzed in phosphate buffer solutions to the corresponding saccharide derivatives, diamines, and carbon dioxide at 27 °C more quickly than polyurethanes 15 and 14β , derived from 1,4:3,6‐dianhydro‐ D ‐glucitol ( 11 ) and methyl β‐ D ‐glucofuranosidurono‐6,3‐lactone ( 10β ), respectively:28, 29…”
Section: Introductionmentioning
confidence: 99%
“…In concert with the depletion of oil resources, increasingly greater attention has been directed to effective utilization of plant‐biomass as alternative, renewable resources that can be steadily supplied and used for polymer syntheses. We also have been investigating polymer syntheses from renewable resources22–24 and biopolymer–synthetic polymer hybrids as well 25–28. In particular, we have been engaged in biodegradable polymer syntheses using three stereoisomeric 1,4:3,6‐dianhydrohexitols, that is, 1,4:3,6‐dianhydro‐ D ‐glucitol ( 1 ), 1,4:3,6‐dianhydro‐ D ‐mannitol ( 2 ), and 1,4:3,6‐dianhydro‐ L ‐iditol ( 3 ) 29–33.…”
Section: Introductionmentioning
confidence: 99%